Key to Mexican and Central American genera of Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) with erect setae on elytral surface, excluding the Caribbean Islands - Monné, Miguel A.; Santos-Silva, Antonio; Monné, Marcela L. (Zootaxa, 2020)
A key for identification of the 34 genera of Acanthocinini with erect setae on the elytra occurring in Mexico and Central America (excluding the Caribbean Islands) is provided. Leptrichillus Gilmour, 1960 is synonymized with Lepturgotrichona Gilmour, 1957, and Leptrichillus minutus Gilmour, 1960 is synonymized with Lepturges stigmaticus Bates, 1881 (currently, Lepturgotrichona stigmatica).